2017
DOI: 10.1016/j.jhazmat.2015.12.071
|View full text |Cite
|
Sign up to set email alerts
|

Transport of stabilized iron nanoparticles in porous media: Effects of surface and solution chemistry and role of adsorption

Abstract: Carboxymethyl cellulose (CMC) stabilized zero-valent iron (ZVI) (CMC-ZVI) nanoparticles have been extensively tested for remediation of soil and groundwater. This study investigated effects of iron oxide and aluminum oxide on retention and transport of CMC-ZVI nanoparticles, which have a mean hydrodynamic diameter of 155nm. Column breakthrough experiments showed that the metal oxides coatings on quartz sand greatly enhanced particle retention. A mechanistically sounder transport model was proposed by incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(23 citation statements)
references
References 69 publications
2
21
0
Order By: Relevance
“…The model simulation results indicated that once CMC-stabilized nZVI is delivered, 99% of the nanoparticles would be removed by the soil matrix within cm at a groundwater flow velocity of 0.1 m/day, but may travel over m at pore flow velocity of 61 m/day, indicating that the transport distance of the nanoparticles can be controlled by manipulating the injection pressure. Zhang et al (2016) proposed a mechanistically sounder transport model by incorporating a Langmuir-type adsorption rate law term into the classic convection-dispersion equation with the adsorption parameters derived from independent batch adsorption experiments. The model allows for a quantitative evaluation of the role of adsorption, which is an important mechanism for the retention of stabilized nZVI, especially for soils rich in metals.…”
Section: Transport Of Stabilized Nzvimentioning
confidence: 99%
“…The model simulation results indicated that once CMC-stabilized nZVI is delivered, 99% of the nanoparticles would be removed by the soil matrix within cm at a groundwater flow velocity of 0.1 m/day, but may travel over m at pore flow velocity of 61 m/day, indicating that the transport distance of the nanoparticles can be controlled by manipulating the injection pressure. Zhang et al (2016) proposed a mechanistically sounder transport model by incorporating a Langmuir-type adsorption rate law term into the classic convection-dispersion equation with the adsorption parameters derived from independent batch adsorption experiments. The model allows for a quantitative evaluation of the role of adsorption, which is an important mechanism for the retention of stabilized nZVI, especially for soils rich in metals.…”
Section: Transport Of Stabilized Nzvimentioning
confidence: 99%
“…Interest in the application of nanoscale zero-valent iron (nZVI) particles in remediation of point-source polluted sites has grown dramatically in recent years [1,2]. nZVI are characterized by a large surface area, high reactivity, and possible mobility in the subsurface due to its small size.…”
Section: Introductionmentioning
confidence: 99%
“…where L is the length of porous media (m), and C/C 0 is the maximum normalized effluent concentration. Other models incorporate a Langmuir-type adsorption isotherm in the traditional advection-dispersion equation (Zhang et al 2017). It is also important to note that in porous media, the mobility of iron particles can be affected by the presence of biofilm (Basnet et al 2016;Crampon et al 2018).…”
Section: Injection Of Particular Solidsmentioning
confidence: 99%